Znaczenie funduszy strukturalnych w rozwoju infrastruktury technicznej na obszarach wiejskich - Oliński, Marian (The Role of Structural Funds in the Development of Technical Infrastructure in Rural Areas, 2005)
One of the most important and fundamental growth determinants of rural areas is dimension and quality of technical infrastructure. The main source of financial support in rural areas is the European Regional Development Fund. The rural communes may use this fund only under the circumstances which qualify the proposed investments under the activities and objectives enclosed in the Integrated Regional Operational Programme.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 144-148